Analysis of the Impact of UX (User Experience) Design on E-Commerce Website Conversion - Husna, Wahyu Asmaul; Wibowo, Ari Purno Wahyu (International Journal of Economics Development Research (IJEDR), 2024)
User Experience (UX) design plays a crucial role in the success of e-commerce websites. This research analyzes the impact of UX design on visitor conversion rates through a literature review of six reference papers. The analysis results show that UX elements such as intuitive navigation, website loading speed, responsive design, content personalization, and ease of checkout significantly positively affect conversion rates. Poor UX, indicated by high bounce rates and high exit rates, hinders conversion, while good UX increases user engagement and encourages repeat purchases. Additionally, the referenced studies emphasize the importance of understanding user demographics and selecting the appropriate e-commerce platform to design a more personalized and effective user experience. These findings provide strong evidence that investment in UX is highly valuable for e-commerce businesses, helping to increase conversions, build stronger customer loyalty, and achieve long-term success in the digital world.